Effects of rice bran feruloyl oligosaccharides on gel properties and microstructure of grass carp surimi. (1st May 2023) - Wang, Yue; Wang, Dujun; Liu, Jinbin; Yu, Xiaohong
Graphical abstract: Highlights: Rice bran FOs significantly improved the breaking force and WHC of grass crap surimi. Rice bran FOs enhanced the integrity of the myofibrillar protein MP gel network. Rice bran FOs promoted surimi gel microstructure compact and smooth. Abstract: Effects of feruloyl oligosaccharides (FOs) from rice bran on the gel properties, microstructure, and sensory properties of grass crap surimi gel were investigated. The results showed that FOs decreased the whiteness of surimi gel, and improved the water-holding capacity and breaking force of surimi gel. According to the texture analysis, the hardness and chewiness of surimi gel significantly increased by adding 0.3% FOs, but had no significant effect on the springiness and cohesiveness. The changes in AFM images indicated that FOs made myofibrillar protein aggregated and uniformly distributed. The SEM micrograph revealed that the 0.3% FOs group had the most compact and ordered network structure. Additionally, sensory characteristics suggested that FOs reduced off-odor from freshwater fish and remained fish delicious taste. This study provides a new prospect for the potential commercial application of FOs as a health gel enhancer in surimi products.